Estimativa da área e capacidade de retenção foliar de calda em citros - Barbosa, Giselle Feliciani; Nais, Juliana; Ferreira, Marcelo da Costa [UNESP] (My University, 2013)
This work was done to determine the maximum amount of liquid that the citrus leaves can hold back and compare alternative methods for estimating leaf area with the standard method of integrating electronic image. The alternative methods were leaf mirroring on paper and leaf digitalization and imagine analyzes. The spray retention capacity was evaluated with mitecide sprayed with cyhexatin (Sipcatin 500 CS) plus the treatments: combination of two adjuvants (mineral oil - Assist and vegetable oil - Veget'Oil) and two concentrations (10 and 15 mL of adjuvant L-1). The methods for estimating leaf area assessed do not differ between them. The maximum retention of liquids for the leaf occurred when vegetable oil in the application was used.

O objetivo deste trabalho foi determinar a capacidade de retenção de calda pelas folhas de citros e comparar métodos alternativos de estimativa de área foliar com o método padrão do integrador eletrônico de imagem. Os métodos alternativos foram o do espelhamento em papel e da digitalização e análise da imagem. A capacidade de retenção da calda foi avaliada com caldas acaricidas com o produto cyhexatin (Sipcatin 500 SC), acrescido dos tratamentos: combinação de dois adjuvantes (óleo mineral - Assist e óleo vegetal - Veget’Oil) e duas concentrações (10 e 15 mL de adjuvante L-1 de calda). Os métodos de estimativa da área foliar avaliados não diferem entre si. A retenção máxima de líquidos pela folha ocorreu quando utilizou-se óleo vegetal na calda aplicada.
Citrus leaves area determination and its spray retention capacity
Keywords: Adjuvant; Citrus sinensis; Leaf area estimation; Spraying